Sustainability approach in modeling and improvement of finger type slug catcher in gas processing plant - Ahmad Khairul Azhar, Ahmad Kamal (2011)
This thesis studies the slug flow behavior inside a finger type slug catcher.Slug exists when two phase are flowing together.Slug can cause damage and unnecessary shut down of process equipment.To handle slug,finger type slug catcher is used as it is a liquid receiving facility designed to handle large volume of liquid and to stabilize it.Finger type slug catcher used the gravity settling separation method to separate the gas and liquid phase of the flow.Finger type slug catcher can be massive in size,and the gas recovery percentage is difficult to maximize.Unbalance mass distribution of the natural gas inside the slug catcher contribute to the low gas recovery inside the slug catcher. The objective of this research is to increase the mass distribution of the flow on the original slug catcher design hence increasing the efficiency of the separation. A base model is design for the original finger type slug catcher using Gambit and several modifications can be added from there named modify design.The proposed modification for the original slug catcher design is the addition of one equalizer header and the T-junction separation at inlet manifold.Original and modified slug catcher designs are tested for its efficiency by using Fluent. Both the velocity magnitude and phase volume fraction will be taken as result to compare the effectiveness of the modification.Result from the original slug catcher design show an unbalance mass distribution by analyzing its velocity magnitude.Poor separation cause by both the unbalance mass distribution and unsuitable pressure inside the original slug catcher lead to low separation of gas.Modify design of the slug catcher show a positive response of the velocity magnitude and suitable pressure on the inlet manifold.T-junction separation at inlet manifold cause the velocity magnitude to be even on both of the pipe and mass distribution balance are greatly increased.The modifications of the original design thus increase the effectives of finger type slug catcher by 6%.